The Interplay Between Career Development and Employee Turnover: A Study in The Hospitality Industry - Shreya, Shreya; Yadav, Preeti (Journal of Neonatal Surgery, 2025)
The hospitality business in Rajasthan, a state that is renowned for its abundant cultural history and strong tourist sector, makes a substantial contribution to the economy of India. A high personnel turnover rate, on the other hand, is one of the most significant difficulties that this sector is now facing. This turnover rate has a detrimental influence on operational efficiency, service quality, and overall organizational stability. The purpose of this research is to investigate the relationship between the availability of career advancement possibilities and the rate of employee turnover in the hotel industry in Rajasthan. This study used a mixed-methods approach to investigate the elements that are considered to be significant predictors of employee turnover. These factors include the availability of training programs, the clarity of promotion tracks, and overall work satisfaction. Quantitative data was gathered by means of structured questionnaires that were sent to two hundred workers in Rajasthan's hospitality centers, which included Jaipur, Udaipur, Jodhpur, and Jaisalmer. In addition to this, qualitative insights were gleaned via semi-structured interviews conducted with HR experts while also included workers. According to the findings, there is a significant negative association between career development activities and turnover intentions. Employees see restricted training options and uncertain career advancement as main issues that drive unhappiness and departure from their current position. It seems from the data that hospitality firms have the potential to dramatically lower employee turnover rates by making investments in organized career development programs and addressing the specific problems that are associated with seasonal employment in the state. Through the use of this study, stakeholders in the hospitality sector in Rajasthan are provided with practical insights that can be used to build successful strategies for staff retention. In conclusion, the research highlights the significance of connecting organizational policies with employee objectives in order to cultivate a workforce that is both stable and motivated throughout its whole.